GR/HDAC2/TGFβR1 pathway contributes to prenatal caffeine induced-osteoarthritis susceptibility in male adult offspring rats. (June 2020) - Li, Jing; Xiao, Hao; Luo, Hanwen; Tan, Yang; Ni, Qubo; He, Chunjiang; Magdalou, Jacques; Chen, Liaobin; Wang, Hui
Abstract: Prenatal caffeine exposure (PCE) induces developmental toxicity of multi-organ and susceptibility to multi-disease in offspring. However, the effects of PCE on osteoarthritis susceptibility in adult offspring and its intrauterine programming mechanism remain to be further investigated. Here, we found that PCE induced susceptibility to osteoarthritis in male adult offspring rats, which was related to the inhibited function of cartilage matrix synthesis from fetuses to adults. Meanwhile, PCE consistently downregulated the H3K9ac and expression levels of transforming growth factor β receptor 1 (TGFβR1), and then blocked TGFβ signaling pathway, which contributed to the suppressed cartilage matrix synthesis. Moreover, the high level of corticosterone caused by PCE reduced the H3K9ac level on TGFβR1 promoter region through acting on glucocorticoids receptor (GR) and recruiting histone deacetylase 2 (HDAC2) into the nucleus of fetal chondrocytes. Taken together, PCE induced osteoarthritis susceptibility in male adult offspring rats, which was attributed to the low-functional programming of TGFβR1 induced by corticosterone via GR/HDAC2 signaling. Highlights: Prenatal caffeine exposure (PCE) caused osteoarthritis susceptibility in offspring. The low-expressional TGFβR1 contributed to the inhibited cartilage matrix synthesis. PCE induced-high corticosterone decreased H3K9ac of TGFβR1 via GR/HDAC2 signaling.